Challenges and advances in translating gene therapy for hearing disorders. Issue 1 (2nd January 2020) - Büning, Hildegard; Schambach, Axel; Morgan, Michael; Rossi, Axel; Wichova, Helena; Staecker, Hinrich; Warnecke, Athanasia; Lenarz, Thomas
ABSTRACT: Introduction : Although sensorineural hearing loss (SNHL) is the most common neurodegenerative disease in humans, no approved pharmaceutical interventions are currently available. The progression of inherited as well as acquired forms of hearing loss can be altered by transferring single genes to distinct cell types of the ear inner. The inner ear is an attractive target for gene therapy given its small size and localized anatomic nature, which is accessible through routine surgical approaches. Areas covered : SNHL is the symptom of a diverse group of disorders with specific requirements regarding the timing of therapeutic intervention, the target cell population, the delivery system and, of course, the therapeutic active "substance'. Expert opinion : Despite these challenges, which will be discussed in the following paper, the first human gene therapy clinical trial for an inner ear disease is already initiated, making this the perfect time to translate a great variety of therapeutic approaches from the laboratory into clinical routine.